'It's much harder than I thought': Facilitating a singing group for people with Parkinson's disease. Issue 1 (1st May 2020) - Forbes, Melissa; Bartlett, Irene
A university-based, international research project investigating the effects of regular singing group activities for people with Parkinson's disease (PD) provided a unique opportunity to capture the lived experience of three facilitators of Australian-based singing groups. Using a phenomenological approach, data were collected via facilitators' reflective journals of singing group activities together with their oral reports at a symposium at the conclusion of the larger research project. Data analysis revealed the skills and attributes described by the three facilitators and the challenges they experienced. Results indicate that targeted skills training around a knowledge of voice function and awareness of the physical and emotional challenges faced by people with PD could assist facilitators to develop best practice interventions.